Ayahuasca and research related to the religious context: integrative review (Research, Society and Development, 2022)
The study aims to identify research in the health area on the use of ayahuasca related to the religious context, from 2017 to 2021. Descriptive research, of the Integrative Literature Review (RIL) type. As inclusion criteria, we used articles available in Portuguese, English and Spanish, complete articles and that were between the years 2017 to 2021. The databases used were the Virtual Health Library (VHL) and PubMed. Data collection was performed using the adapted Ursi form and data analysis using Bardin. 9 articles were selected. Quantitative analysis identified 6 (66.6%) in pubmed and most of the year 2020. 4 (44.4%) were built mainly by pharmacists. From the qualitative analysis, four thematic categories were listed: Ayahuasca and treatment for chemical dependency; Ayahuasca in the treatment of psychological disorders; The legitimacy and concern with the commercialization of ayahuasca; Ayahuasca and Spirituality. The RIL allowed identifying national and international scientific evidence on the use of ayahuasca in the religious context, thus making it possible to achieve the objective of the research. Despite still being considered a little discussed and stigmatized subject, the articles allowed the identification of relevant findings.